A política de assistência estudantil a partir da execução do programa auxílio permanência no Instituto Federal de Alagoas - campus Palmeira dos Índios: a permanência pelo auxílio - Borges, Cintia Cinara Morais (2015)
The objective of this study is to analyze the Student Assistance Policy at the Federal Institute of Alagoas, campus Palmeira dos Indios through the implementation of the aid program permanence and its impact on academic life of students of the degree in Civil Engineering. To this end, 44 students were addressed to the aforementioned course, who responded to a questionnaire on student politics. The views of students on politics were investigated, what the amount of aid remaining in their academic lives and which knowledge of them (students) on the sectors involved with the student assistance on the campus of Palmeira dos Indios. In the first chapter was held short analysis of the impact of corporate restructuring on the requirements of vocational training in Brazil and the public policies, particularly in the Brazilian Education Policy. The second chapter covers considerations about the Assistance Policy Student describes the trajectory of student politics in Brazil. The last chapter concerns the discussion of the Student Assistance Policy in IFAL - campus Palmeira dos Indios, where the survey data are analyzed. In conclusion, it can be inferred that the Student Assistance Policy has evolved in Brazil, primarily through the regulation of PNAES (2010) to help reduce inequalities and residence of students in the courses of IFES. However, students partially know the nuances of policy, which requires a work of professionals involved with the student assistance.